Testing the Effects of Deterrence Communications on Illegal Marijuana Dealing: An Experimental Study - Yim, Ha-Neul (Crime & delinquency, 2024)
Recent experiments have shown that deterrence communication can lead individuals to update their sanction perceptions. However, there remains the question of whether different forms of deterrence communication influence sanction perception updating for illegal marijuana dealing. Using data from an experiment with a nationwide sample of 498 adults, we examined whether a message unpacking sanction risk leads to sanction perception updating and whether this updated risk perception influences drug dealing intentions. The findings revealed that the unpacking message did not influence perceived certainty and severity and intentions to offend, and the risk perceptions did not mediate the impact of the unpacking message on intentions to offend. The implications of the findings are discussed.